Multiple Roles of Vestigial-Like Family Members in Tumor Development - Yamaguchi, Noritaka (Frontiers in Oncology, 2020)
Vestigial-like family (VGLL) members are mammalian orthologs of vestigial gene in Drosophila, and they consist of four homologs (VGLL1–4). VGLL members have TDU motifs that are binding regions to TEA/ATSS-DNA-binding domain transcription factor (TEAD). Through TDU motifs, VGLL members act as transcriptional cofactors for TEAD. VGLL1-3 has single TDU motif, whereas VGLL4 has two tandem TDU motifs, suggesting that VGLL4 has distinct molecular functions among this family. YAP and TAZ (YAP/TAZ) are well-known tumorigenic cofactors for TEAD, and aberrant activation of YAP/TAZ is critically involved in tumorigenesis. Emerging evidence has shown that the aberration of VGLL members is also involved in tumor development. The overexpression of VGLL1 promoted anchorage-independent growth in prostate tumor cell lines. Furthermore, increased expression of VGLL1 enhanced metastasis in gastric tumor cells. Elevated VGLL3 expression showed positive correlation with poor prognosis in gastric tumor patients. Importantly, gene alterations and amplification of VGLL1-3 were observed in various types of tumor. Most studies have strongly suggested that VGLL1-3 has tumorigenic functions. In contrast, the tumor-suppressing role of VGLL4 in various tumors has been demonstrated; mechanistically, VGLL4 competes with YAP/TAZ for TEAD binding. It has also been reported that VGLL4 suppresses tumorigenic transcription factors, TCF4 and STAT3. The inactivation of VGLL4 is caused by microRNA-mediated gene silencing or CDK1-mediated phosphorylation. These observations indicate that VGLL members play crucial roles in tumor development and that these members are candidate targets for tumor treatment. In this review, I summarize the multiple roles of VGLL members in tumor development.